EARNINGS MANAGEMENT AT THE COMPANY THROUGH DEFERRED TAX ASSETS RESERVES - Oetama, Nathania Sherly; Sulistiawan, Dedhy (STIE Kusuma Negara, 2020)
Earnings management is the company's actions taken so that the company reaches a certain level of profit. Many ways can be done by companies in the framework of earnings management, one of which is to change the method or conduct a backup policy that has not been or not regulated how and the amount. One way for a company to carry out its profit management is by reserving deferred tax assets. Uncertainty over the income tax that must be paid by the company causes the regulator to allow management to make allowances with each other's valuation. Therefore, this can be one of the ways companies do profit management. This study uses non-financial companies listed BEI in 2016-2018 as research samples. The sample used must recognize deferred tax assets or deferred tax liabilities in their financial statements. Samples that pass the criteria will be tested with multiple linear regression to find out what accounts affect the reserves and whether there are indications that the company is doing earnings management. The results show that the provision for deferred tax assets themselves is affected by deferred tax assets from both fiscal losses and other records. This study also shows an indication of earnings management through the provision of deferred tax assets carried out by the company.